(3GdJOHjQGJ GdYbdjI aj GdSjGSGJ GdeOfjIs - (3eMeO Hf MHjH Gddg GdeYQha HJQcI GdCUagGfj, CHh MGeOs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf deG fXQJ ai GdcJH GdeYehdI ai GdMceI GdSjGSg ef CLRGA GdYdhe GdMbjbjI hJCedJ ai ebGUOgG GdJi bQQhgG HGdCOdI GdYbdjI s
(3BNQgG (B:s
(3bGd GdfHi Ydjg GdSdGe ef CUHM hgeheg ge hGMO caGg Gddg gehe GdOfjG hdBNQI s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(1212 / 2 (3b(B) s
Keywords: (3GdSjGSI hGdGLJeGYs